Solution sets of different methods on the 20-objective LSMOP4. (a), (b), (c), (d), (e), (f), (g), (h), (i), (j) and (k) are TS-SSA, FDV, LMOEADS, IMMOEAD, DGEA, LERD, MOCGDE, AGEMOEAII, HEA, SGECF and UCLMO on 20-objective LSMOP4. - Xiaozhi Du (20890101) (2025)
Solution sets of different methods on the 20-objective LSMOP4. (a), (b), (c), (d), (e), (f), (g), (h), (i), (j) and (k) are TS-SSA, FDV, LMOEADS, IMMOEAD, DGEA, LERD, MOCGDE, AGEMOEAII, HEA, SGECF and UCLMO on 20-objective LSMOP4.